Lower body negative pressure treadmill exercise is more comfortable and produces similar physiological responses as weighted vest exercise - Macias, B. R.; Groppo, E. R.; Bawa, M.; Tran Cao, H. S.; Lee, B.; Pedowitz, R. A.; Hargens, A. R. (International Journal of Sports Medicine, 2007)
Lower body negative pressure (LBNP) treadmill exercise can generate a hypergravity load on the lower body that may improve athlete performance by mechanical and cardiovascular adaptations. This study compared the cardiovascular responses, subjective exertion and discomfort levels produced by LBNP exercise with those generated by a weighted vest (WV). We hypothesized that LBNP exercise is more comfortable than WV exercise at comparable levels of exercise. Nine subjects exercised on a treadmill at nine conditions, at 5.5 mph for 15 minutes, in which they ran in random order to avoid confounding effects: 100 %, 110 %, 120 %, 130 %, and 140 % body weight (BW), the latter four conditions were achieved by either LBNP chamber or WV. Heart rate (HR) and oxygen consumption (V·O2) were monitored continuously using ECG and open circuit spirometry. At the end of each test, subjects were asked to give discomfort and exertion scores using a ten-point visual analog scale (10 = maximal discomfort and exertion). For both HR and V·O2, no significant differences were observed between LBNP and WV. Subjects reported significantly higher discomfort levels when exercising with the WV than with the LBNP at 120 % BW (5.1 ± 0.55 vs. 3.1 ± 0.64; p < 0.05), 130 % BW (6.2 ± 0.42 vs. 2.3 ± 0.44; p < 0.01) and 140 % BW (6.9 ± 0.27 vs. 4.7 ± 0.60; p < 0.01), while maintaining similar exertions at all conditions. Based on these results, LBNP exercise is more comfortable than standard WV exercise, while maintaining similar exertion, HR and V·O2 values.